Foreign ownership and firm hazard during crises: the moderating role of industry’s technological intensity - Varum, Celeste Amorim (2010)
Despite foreign and domestic firms have been found to differ on survival and exit risks during crises, we believe that other factors may moderate this foreignness effect, as the technological intensity of the industry. The results show that foreign firms operating in more technology-intensive industries face lower hazards during crises, so the resulting competitive advantage may offset the uncertainty inherent in innovative activities. The conclusions are important for policymakers and managers.